2015
DOI: 10.1016/j.jcrs.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted cataract surgery versus standard phacoemulsification cataract surgery: Outcomes and safety in more than 4000 cases at a single center

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 25 publications
2
92
0
8
Order By: Relevance
“…These surgical platforms, developed primarily for cataract surgery, have demonstrated potential in improving surgical visualization and repeatability [73]. Large-scale clinical trials were conducted to evaluate the efficacy and safety of commercial femtosecond laser modules with OCT guidance [193], [194] and the researchers reported that OCT aided in detection of the anterior and posterior lens surfaces and iris boundaries [193], and that femtosecond laser cataract surgery with OCT guidance resulted in comparable complication rates to manual surgery [193,194]. image-based detection of cancer in in vivo resection beds and excised tissue using histopathology as a gold standard [94] (Fig.…”
Section: Human Anterior Eye Surgerymentioning
confidence: 99%
“…These surgical platforms, developed primarily for cataract surgery, have demonstrated potential in improving surgical visualization and repeatability [73]. Large-scale clinical trials were conducted to evaluate the efficacy and safety of commercial femtosecond laser modules with OCT guidance [193], [194] and the researchers reported that OCT aided in detection of the anterior and posterior lens surfaces and iris boundaries [193], and that femtosecond laser cataract surgery with OCT guidance resulted in comparable complication rates to manual surgery [193,194]. image-based detection of cancer in in vivo resection beds and excised tissue using histopathology as a gold standard [94] (Fig.…”
Section: Human Anterior Eye Surgerymentioning
confidence: 99%
“…[38][39][40] Abell ve ark.nın yaptığı 4.080 gözü içeren büyük bir çalışmada; Catalyst Lazer Sistemi ile cerrahi olan 1.852 gözden 21'inde tamamlanmamış kapsülotomi saptandı. Arka kapsül yırtığı FSL ile cerrahi olan 8 gözde gelişirken, FSL olmayan 4 gözde meydana geldi (İstatistiksel olarak anlamlı değildi).…”
Section: Di̇ğer Kompli̇kasyonlarunclassified
“…Korneal haze FSL olmayan cerrahide 1 gözde görülürken, FSL grubunda 12 gözde meydana geldi (p=0,0009) Unstabil pupil FSL cerrahinde 30 gözde görülürken, normal cerrahide 14 gözde görülmüştür (p=0,003). 38 Ayrıca FSL'de ön kapsülotomi CCC şeklinde olmayıp, lazer enerjisinin veriliş şekli nedeni ile tır-tıklı olmaktadır. Bazen ön kapsül tam olarak açıla-mamakta ve kistotom ile girilerek ön kapsüloto-minin tamamlanması gerekmektedir.…”
Section: Di̇ğer Kompli̇kasyonlarunclassified
“…In reviewing cataract surgery complications rates, it is striking that over 95% of surgeries have no intraoperative complications. 3,8,22 The most frequent intraoperative complications that occur are anterior and posterior capsular tears, followed by dropped lens materials (Table 1). A, 3,7,8,16,22 The most clinically significant of these complications (posterior capsular tears, vitreous loss, and dropped lenses) do not typically occur during the creation of the anterior capsulotomy, but result from capsular trauma during later stages of cataract surgery.…”
mentioning
confidence: 99%
“…3,8,22 The most frequent intraoperative complications that occur are anterior and posterior capsular tears, followed by dropped lens materials (Table 1). A, 3,7,8,16,22 The most clinically significant of these complications (posterior capsular tears, vitreous loss, and dropped lenses) do not typically occur during the creation of the anterior capsulotomy, but result from capsular trauma during later stages of cataract surgery. 22 As FLACS does not remove the necessity for any postcapsulotomy surgical instrumentation, such as use of a sharp phacoemulsification needle, non-dominant-hand instruments, or irrigation and aspiration, it does not remove the possibility of inadvertent damage to the capsule at these stages of surgery.…”
mentioning
confidence: 99%